Orb weaver aggregate glue protein composition as a mechanism for rapid evolution of material properties - Ayoub, Nadia A.; DuMez, Lucas; Lazo, Cooper; Luzaran, Maria; Magoti, Jamal; Morris, Sarah A.; Baker, Richard H.; Clarke, Thomas; Correa-Garhwal, Sandra M.; Hayashi, Cheryl Y.; Friend, Kyle; Opell, Brent D. (Frontiers in Ecology and Evolution, 2023)
Orb web and cobweb weaving spiders in the superfamily Araneoidea are distinguished by their ability to make a chemically sticky aqueous glue in specialized aggregate silk glands. Aggregate glue is an environmentally responsive material that has evolved to perform optimally around the humidity at which a spider forages. Protein components and their post-translational modifications confer stickiness to the glue, but the identities of these proteins have not been described for orb web weavers. Using biomechanics, gene expression data, and proteomics, we characterized the glue’s physical properties and molecular components in two congeners that live in different environments, Argiope argentata (dry southwest US) and A. trifasciata (humid southeast US). The droplets of A. argentata are less hygroscopic than those of A. trifasciata and have proportionately smaller viscoelastic protein cores, which incorporate a smaller percentage of absorbed water as humidity increases. Argiope argentata protein core was many times stiffer and tougher than A. trifasciata protein. Each species’ glue included 30 aggregate-expressed proteins, most of which were homologous between the two species, with high sequence identity. However, the relative contribution and number of gene family members of each homologous group differed. For instance, the aggregate spidroins (AgSp1 and AgSp2) accounted for nearly half of the detected glue composition in A. argentata, but only 38% in A. trifasciata. Additionally, AgSp1, which has highly negatively charged regions, was 2X as abundant as the positively charged AgSp2 in A. argentata but 3X as abundant in A. trifasciata. As another example, A. argentata glue included 11 members of a newly discovered cysteine-rich gene family, versus 7 members in A. trifasciata. Cysteines form disulfide bonds that, combined with the higher potential for electrostatic interactions between AgSp1 and AgSp2, could contribute to the greater stiffness of A. argentata glue. The ability to selectively express different glue protein genes and/or to extrude their products at different rates provides a faster mechanism to evolve material properties than sequence evolution alone.